Synthesis and Antimicrobial Activity of Novel Formazans and Their Tetrazolium Bromides - Vashi, R.T.; Sheth, N.M. (Asian Journal of Chemistry, 2010)
Novel formazans [III(a-l)] have been synthesized by the coupling reaction of diazotized solution of substituted sulfanilamide derivatives with aryl hydrazones of different benzaldehydes in pyridine. The resultant formazans were further cyclized by H2SO4,H2O2/Fe2+, NaBr to prepare the corresponding tetrazolium bromides [IV(a-l)]. The compounds were characterized by 1H NMR, IR and elemental analysis. The compounds were assayed for antimicrobial activity.